2022
DOI: 10.1007/s00228-022-03284-4
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported medication adherence and pharmacy refill adherence among persons with ischemic stroke: a cross-sectional study

Abstract: Purpose To describe and compare self-reported medication adherence assessed with the 5-item version of Medication Adherence Report Scale (MARS-5) and pharmacy refill adherence based on data from the Swedish Prescribed Drug Register (SPDR) among persons with ischemic stroke, and to investigate independent predictors associated with respective assessments. Methods A study questionnaire was sent to persons with ischemic stroke registered in the Swedish Stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…The adherence level in the present study is in line with results shown in previous studies using MARS-5 to study the implementation phase [ 28 , 29 , 31 33 ]. These studies focused on geriatric individuals and/or subjects with ischemic stroke or inflammatory bowel disease who were living at home.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The adherence level in the present study is in line with results shown in previous studies using MARS-5 to study the implementation phase [ 28 , 29 , 31 33 ]. These studies focused on geriatric individuals and/or subjects with ischemic stroke or inflammatory bowel disease who were living at home.…”
Section: Discussionsupporting
confidence: 92%
“…The reported adherence level often varies with the population studied, the time at which the assessment is performed, or which methods are used to assess adherence [9,[34][35][36][37]. As has been shown in previous studies, the repartition of MARS-5 answers was skewed [28,29,31,33], suggesting that a recall bias or response bias cannot be ruled out.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…MARS scores range from 5 to 25, with higher scores indicating greater adherence. A score of ≥23 indicates adherence (Norberg, Sjölander, Glader, & Gustafsson, 2022 ).…”
Section: Methodsmentioning
confidence: 99%